Living Bioelectronics: Strategies for Developing an Effective Long‐Term Implant with Functional Neural Connections. (11th September 2017) - Goding, Josef A.; Gilmour, Aaron D.; Aregueta‐Robles, Ulises A.; Hasan, Erol A.; Green, Rylie A.
Abstract: Existing bionic implants use metal electrodes, which have low charge transfer capacity and poor tissue integration. This limits their use in next‐generation, high resolution devices. Coating and other modification techniques have been explored to improve the performance of metal electrodes. While this has enabled increased charge transfer properties and integration of biologically responsive components, stable long term performance remains a significant challenge. This progress report provides a background on electrode modification techniques, exploring state‐of‐the art approaches to improving implantable electrodes. The new frontier of cell‐based electronics, is introduced detailing approaches that use tissue engineering principles applied to bionic devices. These living bioelectronic technologies aim to enable devices to grow into target tissues, creating direct neural connections. Ideally, this approach will create a paradigm shift in biomedical electrode design. Rather than relying on unwieldy metal electrodes and direct current injection, living bioelectronics will use cells embedded within devices to provide communication through synaptic connections. This report details the challenge of designing electrodes that can bridge the technology gap between conventional metal electrode interfaces and new living electrodes through considering electrical, chemical, physical and biological characteristics. Abstract : Bionic implants using metal electrodes have low charge transfer capacity and poor tissue integration. This progress report provides a background on electrode modification techniques, exploring state‐of‐the art approaches to improving implantable electrodes. The new frontier of cell‐based electronics is introduced, detailing approaches that use tissue engineering principles applied to bionic devices. Living bioelectronics will ultimately create a paradigm shift in biomedical electrode design.